Energy Efficient Smart Street Light System - Gupta, Harshita; Tripathi, Naman; Thorve, Prasad; Lomte, Vina M (International Journal of Computer Sciences and Engineering, 2025)
Conservation of energy is an important aspect that is to be considered while planning a resource utilizing project. Vitality proficient lighting framework is a stage towards an asset productive and helps to maintain sustainable growth. If pedestrians or automobiles, summarized as active traffic elements, are not situated near street lights, it is not vitality proficient to turn them on when the light intensity is higher in surrounding conditions. The basic plan is to switch on street lights only when they are required to the traffic elements thus fulfilling the need of illumination at dark places. The system also allows monitoring of the lights thus checking their proper functioning at all times. A mechanized lighting or Light on Demand (LoD) framework is required to execute moving light. By automating the street light system, light naturally switches on/off in halfway street areas. A considerable amount of energy is conserved by the system and proper illumination of street lights has been achieved with this designed model.